A Mouse Periodontitis Model With Humanized Oral Bacterial Community - Bai, Lan; Chen, Bo-Yan; Liu, Yan; Zhang, Wu-Chang; Duan, Sheng-Zhong (Frontiers in Cellular and Infection Microbiology, 2022)
Increasing evidences suggest periodontitis, characterized by oral dysbiosis, as the critical player on the progression of multiple systemic diseases in human, however there is still a lack of proper mouse model of periodontitis with the colonization of human periodontitis-associated bacteria. We here established a new mouse periodontitis model by combining the ligature of second molars with application of subgingival plaque from periodontitis patients. By 16S rRNA gene sequencing and Taxonomic classification, we found that human periodontitis-associated bacteria efficiently colonized in the mouse model and were enriched in both ligature silk and mouse saliva. Furthermore, the well-recognized periodontal pathogens including Porphyromonas gingivalis (P.g), Fusobacterium nucleatum (F.n), Prevotella intermedia (P.i), and Tannerella forsythia (T.f) were enriched in the new model, but not in ligature-induced periodontitis model or Sham mice. The human periodontitis-associated bacteria potently aggravated mouse periodontitis, as demonstrated by more severe bone resorption and higher expression of inflammatory and osteoclastogenesis genes. In summary, the new mouse periodontitis model paves the way for the research of human periodontitis-associated bacteria.